Quantifying Microstructural Evolution in Moving Magma - Dobson, Katherine J.; Allabar, Anja; Bretagne, Eloise; Coumans, Jason; Cassidy, Mike; Cimarelli, Corrado; Coats, Rebecca; Connolley, Thomas; Courtois, Loic; Dingwell, Donald B.; Di Genova, Danilo; Fernando, Benjamin; et al. (Frontiers in Earth Science, 2020)
Many of the grand challenges in volcanic and magmatic research are focused on understanding the dynamics of highly heterogeneous systems, and the critical conditions which enable magmas to move, or eruptions to initiate. From the formation and development of magma reservoirs, through propagation and arrest of magma, to the conditions in the conduit, gas escape, eruption dynamics and beyond into the environmental impacts of that eruption: we are trying to define how processes occur, their rates and timings, their causes and consequences. However, we are usually unable to observe the processes directly. Here we give a short synopsis of the new capabilities and highlight the potential insights that in situ observation can provide. We present the XRheo and Pele furnace experimental apparatus and analytical toolkit for the in situ X-ray tomography based quantification of magmatic microstructural evolution during rheological testing. We present the first 3D data showing the evolving textural heterogeneity within a shearing magma, highlighting the dynamic changes to microstructure that occur from the initiation of shear, and the variability of the microstructural response to that shear as deformation progresses. The detailed, in-situ, characterization of sample textures presented here therefore represents the opening of a new field for the accurate parameterization of dynamic microstructural control on rheological behavior.